2023
DOI: 10.1002/anie.202309671
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Unfolded Cellular Proteins Using Nanochannel Arrays with Probe‐Functionalized Outer Surfaces

Yujuan Qiao,
Jing‐Jing Hu,
Yuxin Hu
et al.

Abstract: Nanochannel technology has emerged as a powerful tool for label‐free and highly sensitive detection of protein folding/unfolding status. However, utilizing the inner wall of nanochannel array may cause multiple events even for proteins with the same conformation, posing challenges for accurate identification. Herein, we present a platform to detect unfolded proteins through electrical and optical signals using nanochannel array with outer‐surface probes. The detection principle relies on the specific binding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Unfolded proteins are intermediates in the process of protein synthesis that fold into stable proteins in the ER through reactions between sulfhydryl groups. According to the previous literature, 35 bovine serum albumin (BSA) as a classical model was employed to explore the responsiveness of MAT to sulfhydryl groups of unfolded proteins. Circular dichroism (CD) measurements confirmed that the different states of BSA were successfully constructed (Figures S19 and S20).…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Unfolded proteins are intermediates in the process of protein synthesis that fold into stable proteins in the ER through reactions between sulfhydryl groups. According to the previous literature, 35 bovine serum albumin (BSA) as a classical model was employed to explore the responsiveness of MAT to sulfhydryl groups of unfolded proteins. Circular dichroism (CD) measurements confirmed that the different states of BSA were successfully constructed (Figures S19 and S20).…”
Section: T H Imentioning
confidence: 99%
“…High proliferation is an essential feature of malignant cancers, which means that cancer cells need to synthesize more proteins to accomplish cell expansion, and naturally, there are more unfolded proteins as universal markers within the endoplasmic reticulum of cancer cells. Aggregation-induced emission (AIE) luminogen with easy functionalization and high resistance to photobleaching has potential applications in the design of both targeted imaging probes and activation imaging probes. In previous studies, the detection of unfolded proteins in cells was achieved using maleimide (MI) and AIE luminogen, but this probe with single activation could not be used to discriminate normal cells from cancer cells because of the low signal-to-noise ratio (SNR) (Scheme A). Combining targeting and activation capabilities within the single fluorescent probe can increase specificity and SNR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has primarily concentrated on assessing the contribution of the inner-wall probes (PIW), often neglecting the potential impact of those on the outer surface. Recently, it has been demonstrated that analytes can also be detected when they approach the outer surface of solid-state nanochannels, specifically binding with the POS, causing changes in the current signals. This approach allows for detection without the need for analytes to pass through solid-state nanochannels. Generally, nanochannels adorned with POS are commonly subjected to covalent bonding for modification.…”
Section: Outer-surface Functionalized Solid-state Nanochannelsmentioning
confidence: 99%
“…In addition to the ions and small molecules mentioned above, solid-state nanochannels with outer-surface modified probes also facilitate direct and in situ sensitive detection of larger biomarkers including proteins, viruses, and cells. In 2023, Qiao et al used the relatively free space on the outer surface of nanochannel arrays for the detection of protein conformation . In Figure B, a platform employing nanochannel arrays and protein origami structures for the detection of unfolded proteins through both electrical and optical signals was realized.…”
Section: Outer-surface Functionalized Solid-state Nanochannelsmentioning
confidence: 99%
See 1 more Smart Citation